2013
DOI: 10.1002/adfm.201202695
|View full text |Cite
|
Sign up to set email alerts
|

A Large Magnetoresistance Effect in p–n Junction Devices by the Space‐Charge Effect

Abstract: The finding of an extremely large magnetoresistance effect on silicon based p–n junction with vertical geometry over a wide range of temperatures and magnetic fields is reported. A 2500% magnetoresistance ratio of the Si p–n junction is observed at room temperature with a magnetic field of 5 T and the applied bias voltage of only 6 V, while a magnetoresistance ratio of 25 000% is achieved at 100 K. The current‐voltage (I–V) behaviors under various external magnetic fields obey an exponential relationship, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…Compared with magnetic materials research on MR effect of nonmagnetic materials has two outstanding advantages. Firstly large MR effect can be obtained, and secondly the MR shows linear relationship with the applied external magnetic field without saturating even at very high magnetic field of mega gauss field [12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with magnetic materials research on MR effect of nonmagnetic materials has two outstanding advantages. Firstly large MR effect can be obtained, and secondly the MR shows linear relationship with the applied external magnetic field without saturating even at very high magnetic field of mega gauss field [12].…”
Section: Introductionmentioning
confidence: 99%
“…6,[12][13][14] Large MR effects of Ge and Si were mainly found at low temperature and in high magnetic field, but useful devices must operate at room-temperature and in low field (H < 1 kOe). 3,7,9,12 Recently, some room-temperature MR work has also been done. For example, Delmo et al 12 found very large positive MR at room temperature in the In/ i-Si/In structures, exceeding 1000% at 3 T with a bias voltage of 71 V. Schoonus et al 9 demonstrated a positive MR of more than 1000% at the magnetic field of 1.25 T at room temperature in boron-doped Si-SiO 2 -Al structures.…”
mentioning
confidence: 99%
“…1 Recently, many non-magnetic materials have been investigated to enhance the amplitude of MR effect, including semimetallic bismuth (Bi), 2 silver chalcogenide (Ag 2þn Se, Ag 2þn Te), 3 Gallium arsenide (GaAs), 4 Indium antimonide (InSb), 5 Germanium (Ge), 6 and Silicon (Si). [7][8][9][10][11][12] Research on MR effect of these non-magnetic materials has two outstanding advantages compared with magnetic materials. First, large magnitude of MR effect can be obtained, and second, the MR shows linear field dependence, without saturating even at mega-gauss field.…”
mentioning
confidence: 99%
“…Even though some discoveries of large magnetoresistance at room temperature in silicon are reported, magnetoresistance at low magnetic field remains small and the conditions to achieve large magnetoresistance are harsh for conventional device. [24][25][26] Diode-assisted MR offers a platform to design silicon-based magnetic device with large electric response under low magnetic field. In this section, we would propose a kind of silicon-based magnetic logic based on diode-assisted MR, which could solve the compatible problem of magnetic-field-based logic.…”
Section: Silicon-based Magnetic Logicmentioning
confidence: 99%